Improvement of Overhaul Maintenance Management System Based on Failure Method Operation Failure Analysis Using The FMEA Method - Ika Syarah Firmansyah; Suparno Suparno (Institut Teknologi Sepuluh Nopember, 2020)
The Failure Mode and Effect Analysis (FMEA) methodology is a recent systematic approach to analyze and assess identified waste (potential failure mode) on products / services or processes and prevent the frequency of occurrence. This study aims to develop FMEA and is used to analyze the root causes of failure and pareto diagrams to show the most critical identified failures for immediate corrective action. While the Faultr Tree Analysis (FTA) method analyzes system failures from a combination of several systems, levels below and component failures. The results achieved are failure priorities based on the largest RPN value and then action recommendations are taken to address them. The results of this study indicate that in the process of maintaining the plant overhaul there are several wastes. For each waste identified (failure mode) it has been analyzed using Pareto diagrams. To facilitate the assessment of identified waste carried out by respondents from management and experts in their fields through questionnaires. The results will produce a risk priority number (RPN), where the HP TBV HRSG fails to operate at 210, the HP BFP pump is off at 196, the BCP pump has a high Vibration of 192. While the root cause of the potential failure mode has been identified by fault tree analysis (FTA). While some alternative improvements such as: There is a need for training for operators to know and recognize the system, involvement of operators in carrying out repairs / maintenance is important, increasing the availability of spare parts in the field is recommended for the company.